Emigration moods of modern Ukrainians caused by economic problems and a sense of self-restraint (on survey data from the south of Ukraine) - Kalashnikova, Liudmyla; Chorna, Viktoriia; Fesenko, Arthur (Migration & Law, 2021)
This article deals with the problem of spreading emigration moods among modern Ukrainians, caused by a stable sense of their own economic disadvantage and lack of hope for improving the standard of living in the nearest future. Theses moods allow us to evaluate the situation in the categories of “deprivation” concept of poverty: it is the feeling of such limitations (deprivation) is a leading factor in pushing a large number of Ukrainians abroad, to the more prosperous countries in socio-economic terms, especially Western ones. Within the framework of this approach we analysed the results of a special questionnaire survey of residents of three regional centres (Odessa, Mykolaiv, Kherson), conducted by leading sociologists of the South of Ukraine. The survey showed how residents evaluated their standard of living in the territory of the modern South of Ukraine, its prospects for improvement self-esteem of the population and the emigration moods which characterize the specified conditions of life (results are presented by regional, city and age distributions). The study showed that a considerable part of the inhabitants of southern Ukraine really characterized the economic well-being of their families as insufficient in view of the quality of life requirements of the modern civilized people and also expressed doubts about the improvement of the level of their well-being in the future. Unsure about tomorrow, more than half of survey respondents indicated that they were considering moving to a permanent place of residence, with preference given to the Western world, which is now widely associated with wealth and living comfort, in terms of specific migration orientations.